THE INFLUENCE OF BRAND EQUITY ON DECISIONS PURCHASE OPPO BRAND SMARTPHONE BY COMMUNITIES IN BIREUEN DISTRICT - Fina Wahyuni; T. Edyansyah; Halida Bahri; Muchsin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study examines the effect of brand awareness, perceived quality, brand association, and brand loyalty on the decision of the community in Bireuen Regency to purchase Oppo brand smartphones. This study uses primary data obtained by distributing questionnaires to 100 respondents who are Oppo brand smartphone users in the community of Bireuen Regency. The sample collection used is non-probability sampling techniques. The data analysis method used is the multiple linear regression method with the help of SPSS. The results partially show that brand awareness has a positive and significant effect on purchase decision of OPPO brand smartphones by the community in Bireuen Regency, Perception of quality has a positive and significant impact on purchase decisions of OPPO brand smartphones by the community in Bireuen Regency, Brand association has a positive and significant effect purchase decisions of OPPO brand smartphones by the community in Bireuen Regency, and Brand loyalty has a positive and significant impact on purchase decisions of OPPO brand smartphones by the community in Bireuen Regency. Simultaneously, brand awareness, perceived quality, brand association, and brand loyalty significantly affect the purchase decision of the community in Bireuen Regency to purchase OPPO brand smartphones. It is recommended for further researchers to conduct research using other variables that are indicated to influence the purchase decisions of smartphones with other brands such as Xiaomi, Realme, Infinix, and so on.